Association between iron, zinc and protein concentration in the embryo and endosperm regions of rice grain - K. Kampuang (2018)
© All Rights Reserved. This study evaluated the relationships between iron (Fe), zinc (Zn) and protein concentrations in the embryo and endosperm regions of rice grain and its relationship to the total concentrations of these nutrients in brown rice. This study used 12 genotypes of brown rice with wide variations in nutrient concentrations. All genotypes were grown in the same condition and management to avoid environmental effects on nutrients concentration in rice grain. Brown rice was separated into two regions (embryo and endosperm intact with the pericarp) for the nutrient concentration analysis. Nutrient concentrations varied widely, ranging from 47 to 166 mg kg -1 for Zn, 26 to 80 mg kg -1 for Fe and 13 to 25% for protein in the embryo region; and from 13 to 37 mg kg -1 for Zn, 4 to 19 mg kg -1 for Fe and 7 to 13% for protein in the endosperm region. Zn, Fe and protein concentrations were 4.7, 6.5 and 2.0 times higher, respectively, in the embryo than the endosperm. Different relationships between nutrients were found within the embryo and endosperm regions, with correlations found between concentrations of Fe and Zn, Fe and protein and Zn and protein in the embryo, but only between Fe and protein in the endosperm. The concentrations of all nutrients in the endosperm and embryo significantly influenced their total concentration in brown rice, with the endosperm contributing the most. This study confirmed the possibility of the embryo and endosperm binding nutrients differently. In selecting genotypes of brown rice for high levels of nutrients, either for consumption and/or breeding purposes, nutrient levels in both the embryo and endosperm should be considered, as concentrations there, particularly in the starchy endosperm, significantly influenced the overall nutrient concentrations in brown rice.